Determination of Range Parameters of Observation Devices on the Basis of Laboratory Measurements - Jarosław BAREŁA; Mariusz KASTEK; Krzysztof FIRMANTY (Problemy Mechatroniki)
The paper presents two most reliable methods used to determine the range performance of observation devices – Johnson criteria and the TTP model. Johnson criteria is used in NATO standards to determine the probability of detection, recognition and identification of standard NATO targets. TTP model is the latest concept to estimate the range parameters of observation devices, developed and used mainly by US military laboratories. The paper presents simplified description of a method applied to determine the range parameters on the basis of laboratory measurements. It provides the list of parameters and measurement methods required to estimate the detection, recognition and identification ranges according to both Johnson criteria and TTP model. Sample results obtained for thermal cameras and short model analysis are also presented.